CHARF LĀM DALAM CERPEN AʻŪDZU BIKA MINKA KARYA ICHSĀN ʻABDUAL-QUDDŪS (KAJIAN SINTAKSIS) - Yudi Adistiro, Afnan Arummi (Center of Middle Eastern Studies (CMES): Jurnal Studi Timur Tengah, 2017)
This research was conducted to describe the function of "particle lām" attached word class as content syntax function and to know the meanings of appearing in the sentence. This research was done by three steps, such as :1) providing data step by using see note method .2) analysis data step by using devide direct subtance (BUL). 3) Presentation the result of analysis data step by using formal method. According to result of the reseach could be conclused that there were 107 "charf lam" by detail of 61 adhere in noun and 46 data adhere in verb.This reseach was described two materials: 1) the functionparticle lām attached word class as content syntax function in sentence such as : predicate, objective, and adverb. 2) the meanings particle lām such as : a) affirmation, reinforcement, rightful authority, ownership autentic, ownership something that abstract characteristic, the reason, the answering, delivery, the processing become, receiving autentic, receiving something that abstract characteristic, far, transitive, meaning particle ʿalā, meaning particle ilā, meaning particle min.